Capital punishment in precolonial Africa: the authenticity challenge. Issue 1 (2nd January 2018) - Novak, Andrew
ABSTRACT: The modern debate over death penalty abolition in Sub-Saharan Africa frequently references the precolonial period. Has the death penalty truly existed since time immemorial, or is it largely a European imposition? The extent to which precolonial societies used capital punishment is difficult to discern, as many of the anthropological and legal sources that document this period were influenced by colonialism. These sources nonetheless show that the use of capital punishment in the precolonial period was tied to notions of political authority and the spirit world, though legal procedures and even methods of execution varied enormously among societies. This article considers the reliability problems of the extant sources and attempts to make tentative conclusions as to the existence of the death penalty prior to the onset of European rule, bearing in mind that these conclusions are not exhaustive or even necessarily representative of the continent's diversity.